Effect of Different Plucking Systems on Yield and Root Starch Reserve in Two Cultivars of Tea (Camellia sinensis L.) (Journal of Environmental Science and Natural Resources, 2017)
A study was carried out to monitor the effect of different plucking systems on root starch reserve and yield of tea in two cultivars (drought tolerant TRI2025 and moderately drought tolerant TRI2026). Depending on the severity of plucking, four plucking systems were used as treatments namely, mother-leaf plucking, fish-leaf plucking, janam-leaf plucking and estate practice. The cultivar TRI2026 showed significantly higher yield than the drought tolerant cultivar TRI2025. Estate practice produced greater yield in TRI2025 than the other treatments, while in TRI2026 the highest yield was found in fish-leaf plucking system. Although cultivars had no significant effect on root starch reserves, however significantly different found in treatments. About one year after commencing the experiment, for both cultivars higher root starch observed under mother-leaf plucking and the lowest was in janam-leaf plucking.J. Environ. Sci. & Natural Resources, 9(2): 91-95 2016